Multi-DIC setup for the identification of a 3D anisotropic yield surface of thick high strength steel using a double perforated specimen. (September 2016) - Denys, K.; Coppieters, S.; Seefeldt, M.; Debruyne, D.
Highlights: The influence of the boundary conditions and cost function on thick steels using FEMU has been scrutinised. Multiple stereo-DIC systems (multi-DIC) has been combined in the FEMU technique. A 3D Hill 48 yield criterion has been identified using two double perforated specimens measured with multi-DIC. Abstract: Two synchronised stereo-DIC setups, referred to as a multi-DIC setup, have been used to experimentally acquire displacement and strain fields over the front and thickness surfaces of a 10  mm thick S690QL high strength steel. A 3D anisotropic yield surface has been identified, given that full-field information is available in all three directions (lateral, longitudinal and through thickness direction). Since the parameters of a yield surface are only identifiable if the sensitivity with respect to these parameters is substantial, an offsetted double perforated specimen has been designed that has a perforation at both the front and thickness surface of the specimen. Because this specimen generates complex displacement fields, plane stress in this thick high strength steel cannot be assumed any more up to fracture. The latter implies that special attention must be paid to the boundary conditions in the finite element model updating method and consequently the cost function to minimise, hence they have been scrutinised numerically.